2016
DOI: 10.1016/j.freeradbiomed.2016.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of oxidative conversion of Amplex® Red to resorufin: Pulse radiolysis and enzymatic studies

Abstract: Amplex® Red (10-acetyl-3,7-dihydroxyphenoxazine) is a fluorogenic probe widely used to detect and quantify hydrogen peroxide in biological systems. Detection of hydrogen peroxide is based on peroxidase-catalyzed oxidation of Amplex® Red to resorufin. In this study we investigated the mechanism of one-electron oxidation of Amplex® Red and we present the spectroscopic characterization of transient species formed upon the oxidation. Oxidation process has been studied by a pulse radiolysis technique with one-elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
97
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(102 citation statements)
references
References 47 publications
5
97
0
Order By: Relevance
“…A study by Votyakova et al [123] showed interference of this reaction by NADH and reduced glutathione, which also caused an increase in fluorescence. Additionally, peroxinitrite has been shown to oxidize Amplex ® Red in the presence of HRP as well [124]. Different studies have also shown H 2 O 2 -independent oxidation pathways for Amplex ® Red, with e.g., carboxylesterase [125] or peroxinitrite-derived radicals [124].…”
Section: Kits For H 2 O 2 Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Votyakova et al [123] showed interference of this reaction by NADH and reduced glutathione, which also caused an increase in fluorescence. Additionally, peroxinitrite has been shown to oxidize Amplex ® Red in the presence of HRP as well [124]. Different studies have also shown H 2 O 2 -independent oxidation pathways for Amplex ® Red, with e.g., carboxylesterase [125] or peroxinitrite-derived radicals [124].…”
Section: Kits For H 2 O 2 Detectionmentioning
confidence: 99%
“…Additionally, peroxinitrite has been shown to oxidize Amplex ® Red in the presence of HRP as well [124]. Different studies have also shown H 2 O 2 -independent oxidation pathways for Amplex ® Red, with e.g., carboxylesterase [125] or peroxinitrite-derived radicals [124]. HRP has also been used in combination with dihydrorhodamine 6G to form the highly fluorescent rhodamine 6G [126].…”
Section: Kits For H 2 O 2 Detectionmentioning
confidence: 99%
“…Additionally, NADH and reduced glutathione in the presence of HRP can interfere with the measurement [4,48]. Our results indicate that the addition of peroxynitrite can lead to the oxidation of Amplex® Red [44]. The mechanism of this reaction involves the formation of oxidizing radicals (i.e., CO 3 •− and • NO 2 ) from the decomposition of peroxynitrite.…”
Section: Introductionmentioning
confidence: 98%
“…AR-derived radicals can also undergo dismutation to form the secondary transient product. Further de- N -acetylation of that product leads to the formation of resorufin [44]. The Amplex® Red assay is assumed to be highly selective toward H 2 O 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation